Determination of the correlation between tool life for single-tooth and integral milling cutters - Sovilj, Bogdan; Banjac, Dragan; Mitrović, Ratko; Kostić, Ljubiša (Journal of Production Engineering, 1986)
This work analyzes the manufacturing process for the production of cylindrical gears using single-tooth and integral milling cutters. Based on experimental results, a correlation between tool life for single-tooth and integral milling cutters is determined.